EVALUASI KEPUASAN MAHASISWA ATAS IMPLEMENTASI PRINSIP ETIKA PROFESI AKUNTAN PADA AKUNTAN PENDIDIK JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA - Purwaningtyas, Hesty (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to describe the implementation of the principles of professional ethics principles of accountants on accounting educators in the Department of Accounting Faculty of Economics and Business Brawijaya university and the student satisfactory evaluation on the implementation. The ethical principles of accounting profession consists of eight variables, namely the principle of professional responsibility, the public interest, integrity, objectivity, competence and professional prudence, confidentiality, professional behavior and technical standards. This type of research is descriptive-quantitative research. Data collection uses questionnaires which are distributed to 150 respondents. The results of this research indicate that students perceive that accounting educators have implemented ethical principles of the accounting profession. In addition, students are satisfied with the implementation.Keywords: Ethical Principles, Ethics, Accounting Educator, Student Satisfactory